Helicobacter pylori infection, dementia and primary open-angle glaucoma: are they connected? - Tsolaki, Fani (BMC Ophthalmol, 2015)
BACKGROUND: The study aims to elucidate the putative association between various forms of dementia, including Alzheimer’s disease, primary open-angle glaucoma and Helicobacter pylori (H.pylori) infection in all possible combinations. METHODS: We prospectively recruited for the study 156 patients, divided into a dementia group, a glaucoma group and two control groups. All patients were submitted to neuropsychological evaluation aiming to detect dementia, ophthalmological examination, aiming to detect glaucoma, and H.pylori diagnostic testing. The provided data were analyzed with the question of possible correlation between the aforementioned entities. RESULTS: Positive correlations were found between Hp infection and dementia, Hp infection and glaucoma, as well as between dementia and glaucoma. CONCLUSIONS: The study confirmed the hypothesis that neurodegenerative diseases such as dementia and glaucoma are linked to each other and to H.pylori infection.